Pengaruh Digital Marketing, Electronic Word Of Mouth, dan Customer Satisfaction Terhadap Keputusan Pembelian Jasa Nail Art Pada D’Nails & Lash Studio di Kota Batam - Elaine Elaine; Alice Erni Husein (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the influence of digital marketing, electronic word of mouth (e-WOM), and customer satisfaction on purchasing decisions for nail art services at D'Nails & Lash Studio in Batam City, both partially and simultaneously. This study uses a quantitative approach with a descriptive method, involving 100 respondents who have used nail art services with a purposive sampling technique referring to the Lemeshow approach. Data were collected through questionnaires and analyzed through validity and reliability tests, classical assumption tests, regression analysis, and hypothesis testing. The discussion of the research results shows that digital marketing has the most dominant influence on purchasing decisions at 38.9%, which indicates that digital marketing strategies can increase consumer interest and confidence in choosing nail art services. Electronic word of mouth has an influence of 19.4%, which indicates that consumer reviews and recommendations through online media play a role in shaping consumer perceptions and trust, while customer satisfaction has an influence of 24.6%, which reflects that consumer satisfaction is an important factor in driving purchasing decisions and repeat service use. Simultaneously, these three variables are able to explain 72.7% of the variation in consumer purchasing decisions, so it can be concluded that digital marketing, e-WOM, and customer satisfaction have a significant influence on purchasing decisions for nail art services at D'Nails & Lash Studio in Batam City.